The Moderating Role of Self-Efficacy on the Effectiveness of LMS-Based Learning Modules toward Student Learning Outcomes: A Pre-Experimental Study at SMP Laboratorium UM - Muhibuddin Fadhli; Rysky Indra Prasta; Miftah Hur Rahman Zh; Dominic Mahon (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
This research aims to investigate the moderating role of self-efficacy using a pre-experimental one-group pretest-posttest design. Data were collected through cognitive achievement tests (pretest and posttest), a Likert-scale questionnaire measuring perceived LMS module effectiveness, and a self-efficacy questionnaire grounded in Bandura’s three-dimensional framework (magnitude, generality, and strength). Data analysis included paired sample t-tests, Wilcoxon Signed-Rank tests, Spearman correlations, and Moderated Regression Analysis (MRA). Results indicated a statistically significant improvement in learning outcomes following the LMS-based module intervention (t(26) = −8.32, p < .001, Cohen’s d = 1.60). However, neither perceived LMS effectiveness nor self-efficacy demonstrated significant correlations with posttest scores. The moderation analysis revealed that self-efficacy did not significantly moderate the relationship between LMS effectiveness and learning outcomes (R² = .006, p = .839). These findings suggest that while LMS-based modules effectively enhance cognitive achievement, the homogeneity of self-efficacy levels and ceiling effects in posttest scores may have constrained the detection of moderation effects.